Is factor V Leiden a risk factor for thrombotic microangiopathies without severe ADAMTS13 deficiency? - Krieg, Soraya; Studt, Jan-Dirk; Sulzer, Irmela; Lämmle, Bernhard; Hovinga, Johanna A. Kremer (Thrombosis and Haemostasis, 2005)
About 60% of patients diagnosed with acute thrombotic thrombocytopenic purpura (TTP) display a severe ADAMTS13 deficiency. Recently, Raife et al. concluded from a small case series, that factor V Leiden (FVL) might constitute a risk factor for acute thrombotic microangiopathy (TMA) without severe ADAMTS13 deficiency. Therefore, we determined ADAMTS13 activity and FVL carrier-ship in 256 consecutive patients presenting with various forms of acute TMA, including patients diagnosed with TTP or hemolytic-uremic syndrome (HUS). The overall prevalence of FVL was 8.2% (6.25% among patients diagnosed with TTP, and 9% among those with HUS) concordant with the FVL prevalence reported in Europe. FVL was present in 9.9% of patients with ADAMTS13 activity <10% and in 9.7% of those with normal ADAMTS13 activity (>50%). We conclude that FVL is not more prevalent inTMA patients without as compared to those with severe ADAMTS13 deficiency. The prevalence of FVL carriers in certain HUS subgroups (HUS with ADAMTS13 activity >50%) reaching 12.3% suggests that a contributory role of FVL in the pathogenesis of defined forms of HUS needs further study.
Keywords: ADAMTS13 activity; factor V Leiden; HUS; thromboticmicroangiopathy; TTP